Otimização de parâmetros para edição de genoma via CRISPR/CAS9 em citros - Bernardi, Amanda de Carvalho (Universidade Federal de São Carlos, 2017)
The genus Citrus contains a wide variety of fruit-producing species such as oranges, lemons, limes and mandarins that are highly popular in the world. Brazil is one of the main citrus producers, currently leading the world production of oranges. The Brazilian citrus industry is extremely important because of it is great activity that generates jobs, thus contributing to the socioeconomic development of the country. However, the genetic background used in the Brazilian citriculture is still very narrow, with few varieties being cultivated commercially. This is a reflection of the fact that there is still a great difficulty in obtaining superior individuals through traditional breeding due to the limitations presented by the citrus crop. This makes it necessary to develop new technologies, especially those that exploit the already sequenced genomes. One of these technologies is the genome editing, where it is possible to make disruptions in specific points in the genome of a given organism, leading to mutations or substitutions of DNA fragments. Among the various techniques used for genome editing, CRISPR / CAS9 is the most promising because of its ease of use. With its first studies in 2013, there is an increasing number of papers showing CRISPR / CAS9 mediated genome editing in different organisms, including plants. At the present time, for citrus there are works of two groups in which this technology was used to generate mutant plants. Therefore, the application of this technology could be better exploited to take citrus studies in Brazil to another level, with prospects of generation of new varieties. Thus, this project had a central objective to optimize systems for generation of mutants via CRISPR / CAS9 in citrus. In order to explore the existing methodologies for genome editing in plants, constructs of vectors with targets in genes of interest for the study of disease resistance were made using vectors available in the literature. From this initial work, it was possible to propose two improvements for optimization of the process: the use of transient transformation to identify mutations and consequent efficiency of the CRISPR vector and the construction of a new vector for plant genome editing. We were able to evaluate some parameters and to optimize the methodology of transient transformation in sweet orange, resulting in an average of up to 93% of transformed leaf discs. It was also possible to conclude the construction of a new vector for plant genome editing that has the advantages of having reduced size, easy customization in the vector itself and resistance to kanamycin in plants and bacteria. The advances obtained in this work can be applied in studies of several areas not only of citrus, but also of other cultures.
Optimizing parameters for CRISPR/CAS9 genome editing in citrus
Keywords: Clonagem; Edição de genomas; Expressão transiente; Genome edition; Transient transformation; CIENCIAS AGRARIAS::AGRONOMIA